1981
DOI: 10.1093/nar/9.2.293
|View full text |Cite
|
Sign up to set email alerts
|

The secondary structure of the protein L1 binding region of ribosomal 23S RNA. Homologies with putative secondary structures of the L11 mRNA and of a region of mitochondrial 16S rRNA

Abstract: An heterologous complex was formed between E. coli protein LI and P. vulgaris 23S RNA. We determined the primary structure of the RNA region which remained associated with protein LI after RNase digestion of this complex. We also identified the loci of this RNA region which are highly susceptible to TI, SI and Naja oxiana nuclease digestions respectively. By comparison of these results with those previously obtained with the homologous regions of E. coli and B. stearothermophilus 23S RNAs, we postulate a gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…3). This strongly suggested that it may thus be the yeast counterpart of this procaryotic ribosomal protein, even though no equivalent ribosomal component had previously been identified in eucaryotic cells (7,21,33). Our immunological data with anti-Ssm1p antibodies firmly establish that Ssm1p is a structural protein of the yeast ribosome (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…3). This strongly suggested that it may thus be the yeast counterpart of this procaryotic ribosomal protein, even though no equivalent ribosomal component had previously been identified in eucaryotic cells (7,21,33). Our immunological data with anti-Ssm1p antibodies firmly establish that Ssm1p is a structural protein of the yeast ribosome (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…In E. coli, L1 binds to the 23S rRNA of the large 50S subunit (7). The binding property of L1-like proteins to rRNA has been conserved in some archaebacteria (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The putative MjaL1-binding site was synthesized in vitro as part of a 170-nucleotide transcript encompassing positions 2176Ϫ2327 of the 23S rRNA of M. jannaschii (23S rRNA Mja). The EcoL1-binding site on 23S rRNA, which has been identified earlier [34,35], was synthesized in vitro as part of a 180-nucleotide transcript encompassing positions 2076Ϫ2239 of 23S rRNA (23S rRNA Eco ). The dissociation constants and saturation levels obtained for homologous L1-rRNA complexes from M. jannaschii and E. coli were similar to those of the heterologous complexes of MjaL1 and EcoL1 with 23S rRNA Mva .…”
Section: Interaction Of Ribosomal Proteins L1 From M Vannielii M Jmentioning
confidence: 99%
“…There are several structural similarities between the Li binding site on 23S rRNA and the mRNA region around the Lll translation initiation site (8,9). Our previous deletion analysis has identified a region of the mRNA, preceding the Lii initiation site, important for feedback inhibition of Lii and Li synthesis by Li (6).…”
mentioning
confidence: 96%